On politics of the female black body and jongo’s territorialities in the fight against racism - Rufino, Patrícia (Farol, 2021)
This text highlights reflections on black body policies instituted by Jongueira women based on approximations in the cultural practices of Sapê do Norte. It seeks to deconstruct the stereotyped representation of black women’s subordination, emphasizing how communities have historically perceived processes of racial oppression and, in contrast, created strategies to strengthen female leadership. Issues of gender intersectionality are discussed from this perspective, constituting territorialities and contexts of self-assertion. In jongo circles, the body is the premise of the ancestral relationship, of the circularity expressed in the generational cycles that link the past and the present through songs and dances. It is in this context that we draw some parallels about territorialities, ancestors, female circularities.